Normal Physiology. Module 1 - Sukhomlinova, I. E.; Tichonovskay, M. A.; Kirsanova, E. V.; Voteva, W. E.; Сухомлінова, Ірина Євгенівна; Тихоновська, Марина Анатоліївна; Кірсанова, Олена Валентинівна; Вотєва, Ванда Євгенівна (Запорізький державний медичний університет, 2015)
Students’ independent practical work is an important part of the syllabus in the course of Normal Physiology. It helps students to study this fundamental subject. Systematic independent work enables to reach the final goal in the students’ education. It is also important while preparing the students for their future clinical work with patients. These theoretic materials, questions and tests will help students to get ready for the examination.
Keywords: фізіологія; физиология; physiology